Enhancing the quality stability of injection molded parts by adjusting V/P switchover point and holding pressure. (20th January 2021) - Chen, Jian-Yu; Zhuang, Jia-Xiang; Huang, Ming-Shyan
Abstract: The injection molding process is widely used for the mass production of plastic parts. However, as product designs become lighter, thinner and smaller, and the allowable tolerances shrink, the need to improve the quality consistency of the injection molding process has emerged as a critical concern. In mass production, injection molding is typically performed using fixed settings of the machine inputs. However, in practice, the properties of the plastic melt invariably change from batch to batch and even from shot to shot. Consequently, the use of fixed parameter settings fails to guarantee the stability of the molded part quality. Existing quality monitoring and control systems for the injection molding process are often based on pressure information. However, obtaining this information generally requires the installation of pressure sensors within the molding cavity, which is not only expensive and time-consuming, but may also interfere with the injection molding process itself. Accordingly, the present study proposes a quality monitoring and control system for injection molding processes based on the tie bar elongation measurements obtained using a strain gage. In the proposed approach, variations in the tie bar strain characteristic are taken to indicate deviations in the process stability and are used to manipulate the processing parameters accordingly in order to ensure the stability and consistency of the molded part quality. The feasibility of the proposed approach is demonstrated by performing injection molding trials with a two-cavity mold designed to produce tensile test specimens. The experimental results show that the quality of the molded parts varies significantly with the injection speed, velocity-to-pressure (V/P) switchover point, holding pressure, and melt temperature. Among these four parameters, the V/P switchover point and holding pressure induce a particularly rapid dynamic response, and thus provide an effective means of compensating for process deviations from shot to shot. By changing the melt temperature to simulate environmental noise, it is shown that the two parameter settings enable the consistency of the part weight to be restored to a range of 0.01 g within six shots. Moreover, the yield rate is enhanced from 60% to 90%. Graphical abstract: Image 1 Highlights: The V/P switchover point and holding pressure provide an effective means to compensate for the process deviation of successive injections. Appropriate control for the maximum clamping force increment avoids excessive compensation of the part quality caused by environmental noise. The disclosed method can improve the quality consistency and accuracy of injection molded parts without invading mold cavity.